Spectrophotometric Method for the Determination and Biological Activity of Trace Amount of Zn( II ) and Hg ( II ) with Reagent 2 – (6 –Methoxy – 2 – Benzothiazolyl ) azo – 4 , 5 – diphenyl imidazole - Ghali, Azhar Abees; Farhan, Evan (Al-Qadisiyah Journal of Pure Science, 2017)
A direct method has been developed for the spectrophotometeric determination of Zn(II) and Hg(II) using 2–(6 –methoxy – 2 – benzothiazolyl ) azo ] – 4 , 5 – diphenyl imidazole (6-MBTADI) as a complexing reagent . Beer’s law was obeyed over the range from 2- 25μg/mL for Zn(II) and 0.5-13μg/mL for Hg(II). Sandell’s sensitivity and Molar absorptivity have been found to be 0.0582μg.cm-2 and 0.1123x104 L.mol-1.cm-1 for Zn(II), 0.0262μg.cm-2 and 0.7640x104 L.mol-1.cm-1 for Hg(II). Each metals complex were stable for more than 24 hrs under optimized conditions. The limit of detection , relative standard deviations, relative errors and recovery for Zn(II) and Hg(II) complexes were found to be LOD=0.8, 0.45; R.S.D%=3.94 ,1.892; Erel%=2.58, 3.5 and Re%=97.42, 96,5 respectively.